Estudio de prefactibilidad para la instalación de una planta de producción de un detergente líquido a base de saponina de quinua (Chenopodium quinoa) - Huang Sam, Ricardo (2023)
In the present research paper, proposals for improvement related to lean manufacturing will be analyzed with the aim of standardizing production and increasing productivity in the production area of a spinning company, using automation and plant layout tools. Initially, a high variability in production time was identified within the fiber preparation and mixing area, which caused instability and decreased productivity in the zone. After a preliminary analysis, it was found that increasing the amount of fibers used in the process (e.g. from 2 to 3 fibers) resulted in an increase in total production time. Subsequently, a comprehensive evaluation was carried out in the selected company, observing the production processes in order to select the most critical stage of the process within the area to implement an improvement. Finally, different improvement proposals were compared, and it was determined that the most effective and viable ones were automation and a new distribution of the work area. After implementation, an average reduction of 31% in production time was achieved, circulation time was reduced, and monthly production in the area was stabilized.